Can Corrective Information Reduce Negative Appraisals of Intrusive Thoughts in a Community Sample? - Rees, Clare; Austen, T.; Anderson, Rebecca; Egan, Sarah (Cambridge University Press, 2014)
Background: Improving mental health literacy in the general population is important as it is associated with early detection and treatment-seeking for mental health problems. Target areas for mental health literacy programs should be guided by research that tests the impact of improving knowledge of psychological constructs associated with the development of mental health problems. Aims: This study investigated the impact of providing corrective information about the nature of intrusive thoughts on their subsequent appraisal in a community sample. Method: In an online, experimental design, 148 community participants completed measures of obsessive-compulsive symptoms and appraisals (Obsessive Compulsive Inventory-Revised [OCI-R]; Intrusions Inventory [III]). Individuals were instructed to read either a brief informational text about the nature of intrusive thoughts or a control text. All participants then completed post-test measurements of appraisals. Intervention effectiveness was analysed using hierarchical multiple regression. Results: Individuals in the intervention group reported significantly lower levels of maladaptive appraisals than those in the control group (a = .05). Conclusions: The results of this study support the efficacy of provision of brief written information in reducing negative appraisals of intrusive thoughts in a community sample. It suggests a possible role for education about intrusive thoughts as a prevention strategy for obsessive-compulsive disorder.